2015
DOI: 10.1177/0022034515571416
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Antibacterial Dental Adhesive on Multispecies Biofilms Formation

Abstract: Antibacterial adhesives have favorable prospects to inhibit biofilms and secondary caries. The objectives of this study were to investigate the antibacterial effect of dental adhesives containing dimethylaminododecyl methacrylate (DMADDM) on different bacteria in controlled multispecies biofilms and its regulating effect on development of biofilm for the first time. Antibacterial material was synthesized, and Streptococcus mutans, Streptococcus gordonii, and Streptococcus sanguinis were chosen to form multispe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
135
2
3

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(144 citation statements)
references
References 37 publications
2
135
2
3
Order By: Relevance
“…All three-dimensional reconstructions of biofilms were performed with Imaris 7.0.0 (Bitplane, Zürich, Switzerland). The vertical distribution analyses were performed with LAS AF Lite (Leica), and the calculation of bacteria/EPS biomass was performed with COMSTAT (http://www.imageanalysis.dk) [31]. …”
Section: Methodsmentioning
confidence: 99%
“…All three-dimensional reconstructions of biofilms were performed with Imaris 7.0.0 (Bitplane, Zürich, Switzerland). The vertical distribution analyses were performed with LAS AF Lite (Leica), and the calculation of bacteria/EPS biomass was performed with COMSTAT (http://www.imageanalysis.dk) [31]. …”
Section: Methodsmentioning
confidence: 99%
“…Generally speaking, however, with the increase of the amount of antibacterial agent, the mechanical properties and biocompatibility of the material will decrease. QACs belong to a kind of nonrelease antibacterial agent, and the antibacterial effect can be achieved when the dosage is relatively large 32,[44][45][46][47] . While the release antimicrobial agents can achieve better antibacterial effect at a low concentration, however, their extending antibacterial efficiency is low and they may be more toxic toward surrounding environments, the so-called "sudden release effect" [104][105][106][107] .…”
Section: Resultsmentioning
confidence: 99%
“…And then, dimethylaminododecyl methacrylate (DMADDM), NAg, and NACP were incorporated into above adhesive system together and they found that modified bonding agent yielded potent and long lasting antimicrobial properties, and much stronger bond strength after 6 months of water aging than a commercial control 43) . Meanwhile, 5 wt% DMADDM was incorporated into Clearfil SE Bond by Zhang et al It had been observed that adhesives containing DMADDM inhibited the growth, lactic acid production, and Exopolysaccharides (EPS) metabolism of S. mutans biofilm at different stages, with no adverse effect on its dentin adhesive bond strength 44,45) . Besides that, Pupo et al 46,47) performed a study incorporating of quaternary ammonium methacrylate polymer (QAMP) at 5% by mass to Clearfil SE Bond as experimental group, Clearfil SE Bond as negative control group, and Clearfil Protect Bond as positive control group.…”
Section: Adhesive Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…QAMs exert a contact-killing mechanism and have been shown to effectively kill bacteria and inhibit biofilm growth, not only on single-species biofilms, but also on multispecies biofilms [Zhang et al, 2015;Wang et al, 2016]. In addition, the antimicrobial properties are considered to be related to chain lengths and charge densities [Zhou et al, , 2014.…”
Section: Evaluation Of Novel Anticaries Adhesive In a Secondary Cariementioning
confidence: 99%